2002
DOI: 10.1159/000065066
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Angiopoietin-1, Angiopoietin-2, and Tie2 Genes in Normal Ovary with Corpus luteum and in Ovarian Cancer

Abstract: Objective: The recent discovery of angiopoietin-1 (Ang1) and angiopoietin-2 (Ang2) has provided novel and important insights into the molecular mechanisms of blood vessel formation. Ang1 and Ang2 bind with similar affinity to the endothelial cell tyrosine kinase receptor Tie2. Our purpose was to assess the potential role of the Ang/Tie2 system in physiological and pathological angiogenesis in the ovary. Methods:Ang1, Ang2, and Tie2 gene expression in 14 normal ovaries with corpus luteum (CL) and in 19 cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 16 publications
(27 reference statements)
2
31
0
Order By: Relevance
“…ANGPT2 modulates angiogenesis in a cooperative manner with another important angiogenic factor, VEGF [14][15]. Furthermore, Hata et al (2002) suggested that there is a difference in the angiopoietin/Tie2 gene expression between physiological and pathological angiogenesis in the ovary [16]. Angiopoietin-like proteins (ANGPTLs) are a family of proteins structurally similar to the angiopoietins.…”
Section: Figurementioning
confidence: 99%
“…ANGPT2 modulates angiogenesis in a cooperative manner with another important angiogenic factor, VEGF [14][15]. Furthermore, Hata et al (2002) suggested that there is a difference in the angiopoietin/Tie2 gene expression between physiological and pathological angiogenesis in the ovary [16]. Angiopoietin-like proteins (ANGPTLs) are a family of proteins structurally similar to the angiopoietins.…”
Section: Figurementioning
confidence: 99%
“…Elevated Tie2 levels were detected in breast, gastric, and endometrial cancers (35 -37). In contrast, decreased Tie2 level was found in ovarian carcinoma and lung cancer (10,38). Some authors found correlation between Tie2 level and malignancy (e.g., in gastric cancer), whereas others in ovarian cancer did not (11,39).…”
Section: Discussionmentioning
confidence: 91%
“…HR, hazard ratio; OS, overall survival; PFS, progression-free survival; PFS-2, time to second progression event; TSST, time to second subsequent treatment. (8) 101 (22) Treatment-emergent adverse events with ≥5% difference in incidence between arms Localized edema 122 (27) One approach to addressing these challenges suggested by the EMA is to assess the durability of treatment effect by evaluating postprogression endpoints such as PFS-2 and time to second subsequent therapy (TSST) [27,30]. The TRINOVA-1 study is among the first to demonstrate that an antiangiogenic therapy significantly delayed the time to second progression (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The angiopoietin axis is distinct from the VEGF pathway; angiopoietin 1 (Ang1) and angiopoietin 2 (Ang2) regulate angiogenesis and vascular remodeling by interacting with the endothelial receptor tyrosine kinase, Tie2 [5]. Evidence suggests that the Ang2 pathway plays a role in the pathophysiology of ovarian cancer [6][7][8] and upregulation of Ang2 is correlated with poor prognosis in women with recurrent ovarian cancer [9]. Several antiangiogenic agents that target the VEGF pathway have been shown to improve progression-free survival (PFS) in patients with ovarian cancer; however, a statistically significant improvement in OS has not been demonstrated [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%